Prescribing patterns of antimicrobial agents for surgical site infections at 1 Military Hospital and Mankweng Hospital - Mathobela, Caswell Kwena Kedishi (My University, 2018)
Refer to the document
Thesis (M.Sc. (Pharmacology)) -- University of Limpopo, 2018.
Keywords: Antimicrobial agents; Antimicrobial resistance; Microorganisms; Anti-infective agents; Surgery, aseptic and antiseptic; Pharmacology